2020
DOI: 10.1002/ehf2.13126
|View full text |Cite
|
Sign up to set email alerts
|

Clinical effects of cardiac contractility modulation in heart failure with mildly reduced systolic function

Abstract: Aims Increasing attention is being given to patients with heart failure and ‘mid‐range’ left ventricular ejection fraction (LVEF, ≥40% and <50%) for whom there are no approved therapies that improve prognosis. We aim to assess for the first time the effects of cardiac contractility modulation (CCM) therapy in this patient population. Methods and results We assessed the effects of 6‐  month CCM therapy on functional status, exercise tolerance and quality of life in a subgroup of 53 patients with a LVEF of 40–45… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Cardiac contractility modulation (CCM) consists of biphasic high‐voltage bipolar signals delivered to the right ventricular septum during the absolute refractory period and has been shown to improve intramyocardial calcium handling. CCM has improved symptoms, exercise tolerance, and QOL and reduced the rate of HF hospitalizations in patients with ejection fractions between 25% and 45% 166–169 …”
Section: Non‐pharmacological Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac contractility modulation (CCM) consists of biphasic high‐voltage bipolar signals delivered to the right ventricular septum during the absolute refractory period and has been shown to improve intramyocardial calcium handling. CCM has improved symptoms, exercise tolerance, and QOL and reduced the rate of HF hospitalizations in patients with ejection fractions between 25% and 45% 166–169 …”
Section: Non‐pharmacological Therapiesmentioning
confidence: 99%
“…CCM has improved symptoms, exercise tolerance, and QOL and re-duced the rate of HF hospitalizations in patients with ejection fractions between 25% and 45%. [166][167][168][169]…”
Section: Cardiac Contractility Modulationmentioning
confidence: 99%
“…Cardiac contractility modulation (CCM) therapy is a novel device that has been shown to improve cardiac function, exercise tolerance, and quality of life in HFrEF by applying a nonexcitatory stimulus during the absolute refractory period in the right interventricular septum in patients with HFrEF 53 . Exploratory analysis from randomized controlled trials has concluded that the efficacy of CCM therapy is higher in LVEF 35%–45% compared to patients with LVEF 25%–34% indicating its benefit in HFmrEF 54 . Experimental studies have found increased phosphorylation and subsequent activation of titin, a major protein in myocytes responsible for diastolic recoil, on serial endomyocardial biopsies within 3 months of CCM therapy in HFpEF 55 .…”
Section: Role Of Device Therapiesmentioning
confidence: 99%
“…53 Exploratory analysis from randomized controlled trials has concluded that the efficacy of CCM therapy is higher in LVEF 35%-45% compared to patients with LVEF 25%-34% indicating its benefit in HFmrEF. 54 Experimental studies have found increased phosphorylation and subsequent activation of titin, a major protein in myocytes responsible for diastolic recoil, on serial endomyocardial biopsies within 3 months of CCM therapy in HFpEF. 55 A focused trial is yet to be performed in HFpEF and HFmrEF to examine the efficacy of CCM therapy in improving clinical outcomes.…”
Section: Role Of Device Therapiesmentioning
confidence: 99%
“…Cardiac contractility modulation (CCM) is an electrical modality for the treatment of HF, that delivers relatively high voltage and long duration biphasic electrical impulses to the myocardium during the absolute refractory period; therefore, it neither influences the heart rhythm nor the normal propagation of the cardiac action potential across the valves [ 9 , 10 ]. CCM has been shown to increase the ventricular contractility with resultant improvement in the functional capacity of the heart, without the need for an additional oxygen request [ 11 ].…”
Section: Introductionmentioning
confidence: 99%